Draft Eighth Five Year Plan (1990-95) Volume-I Introduction, Sectoral Review and Statements - Planning Commission (Planning Commission, 1991)
The Andaman and Nicobar Group of Islands comprise 572 islands including 266 rocks) with a total geographical area of 8249° Sq. Km. They are situated between 6° and 14° North latitude and 92° and 94° East longitude in toe Bay of Bengal with the 10° channel separating the Andaman group of islands from the Nicobar group. The islands lie in a long, narrow, broken chain approximately North South, in an arc. Port Blair, where the headquarters of this Territory's Administration is located, is 1255 Km away from Calcutta and 1191 Km from Madras. Calcutta and Madras are the two ports through which the islands maintain communication with the mainland. The A&N Islands constitute the most isolated part of India, surrounded by vast stretches of sea in every direction.
Andaman and Nicobar Administration
Planning Commission
Keywords: Agriculture crop Husbandry; Soil & water conservation; Animal Husbandry & Dairy Development; Fisheries; Forestry Sc wild Life; cooperation; Rural Development C»D< & panchayats; Land Reforms; Minor Irrigation; Power Non-conventional Sources of Energy